Area exclosure with moisture harvesting structures relative to only exclosure facilitates the restoration of woody plants in a degraded area in Alaba Kulito, Southern Ethiopia - Shiferaw Alem; Adane Dinku (Journal of Degraded and Mining Lands Management, 2022)
The study aimed to evaluate the effect of area exclosure established in a degraded area with moisture harvesting structures (EX-SWC) relative to the adjacent exclosure area without moisture harvesting structures (EX) in restoring the woody plants. Vegetation data from a total of 30 plots that has an area of 20 m x 20 m, in the EX-SWC and the adjacent EX area were collected, independently. The density of trees and seedlings, diversity, vegetation structure and Importance Value Index (IVI) were analysed. Pearson’s correlation was also used for the data analysis. The Shannon diversity index was 1.6 and 1.57 in the EX-SWC and EX area, respectively. The relative density of trees (578 stems/ha) and seedlings (1530 stems/ha) in the EX-SWC area were relatively higher than the relative density of trees (466 stems/ha) and seedlings (1202 stems/ha) in the adjacent EX area. There was no significant relationship between the number of moisture harvesting structures established in each plot and the relative density of seedlings per plot (p <0.05, R2=0.18). The relative density of seedlings at the lower height classes (1 – 60 cm) in the EX-SWC area was relatively higher than the adjacent EX area. The IVI result for most of the recorded species in the EX-SWC area was also relatively higher than in the EX area. The overall results showed that the implemented moisture harvesting structures facilitated the regeneration of woody plants in the degraded area. Therefore, we recommend implementing soil and water conservation structures in degraded area restoration projects to facilitate the regeneration of woody plants.